Učinki vadbe na domu ob pomoči vaj v pisni in video obliki pri bolnikih po možganski kapi - Bizovičar, Nataša (Rehabilitacija (Ljubljana), 2016)
Background: Supervised rehabilitation treatment can significantly improve the functional recovery over a longer period of time in patients after stroke. Tele-rehabilitation technology allows the use of rehabilitation services in the patient's home environment. The purpose of our pilot study was to test the effectiveness of continuing exercise at home after discharge from inpatient rehabilitation by using a of tele-rehabilitation service. Methods: The study included 10 patients after the first stroke. Upon discharge from the inpatient rehabilitation the patients were randomized into the test group and the control group; there were five patients in each group. The test group received tele-rehabilitation treatment in the form of movies under the supervision of a therapist for 3 months after discharge. The control group received exercises in written form, which they performed without the supervision of a therapist in their home environment. The assessments (passive range of joint motion, muscle tone in the upper limb, pain and motor function) were performed at the time of discharge in the rehabilitation hospital and in the home environment after 3 months of training. Results: There was an improvement in function of the upper limb and general motor function, reduction of muscle tone in the elbow, wrist and finger flexors, and a decrease in pain in both groups after 3 months of training, but there were no statistically significant differences between the groups. Shoulder joint abduction passive range of motion was statistically significantly better in the test group after the training (p = 0,017). Conclusions: Tele-rehabilitation service proved to be an effective and useful method to improve motor skills and joint mobility and also to reduce pain and muscle tone for patients in the chronic period after stroke.
Keywords: motor functions; motorične funkcije; možganska kap; multimedia contents; multimedijske vsebine; Stroke; telerehabilitacija; Telerehabilitation